Qualitative study of guideline panelists: innovative surveys provided valuable insights regarding patient values and preferences - Zeng, Linan; Li, Shelly-Anne; Yang, Mengting; Yan, Lijiao; Helsingen, Lise M.; Bretthauer, Michael; Agoritsas, Thomas; Vandvik, Per O.; Mustafa, Reem A.; Busse, Jason; Siemieniuk, Reed A.C.; Lytvyn, Lyubov; et al. (Journal of clinical epidemiology, 2023)
To explore guideline panelists' understanding of panel surveys for eliciting panels’ inferences regarding patient values and preferences, and the influence of the surveys on making recommendations. We performed sampling and data collection from all four guideline panels that had conducted the surveys through October 2020. We collected the records of all panel meetings and interviewed some panelists in different roles. We applied inductive thematic analysis for analyzing and interpreting data. We enrolled four guideline panels with 99 panelists in total and interviewed 25 of them. Most panelists found the survey was easy to follow and facilitated the incorporation of patient values and preferences in the tradeoffs between benefits and harms or burdens. The variation of patient preferences and uncertainty regarding patient values and preferences reflected in the surveys helped the panels ponder the strength of recommendations. In doing so, the survey results enhanced a rationale for panels’ decision on the recommendations. The panel surveys have proved to help guideline panels explicitly consider and incorporate patient values and preferences in making recommendations. Guideline panels would benefit from widespread use of the panel surveys, particularly when primary evidence regarding patient values and preferences is scarce.